Pleiotropic Properties of Statins in Renal Protection Among Patients with Chronic Kidney Disease: A Review of Current Clinical Evidence - Brzeźniak, Mikołaj; Fitz, Emiliia; Daniek, Justyna; Kręcina, Filip; Kaczmarek, Weronika; Gil, Kacper; Drelich, Krzysztof; Karbowniczek, Aleksander; Mokracka, Julia Maria; Grabarczyk, Alicja (Quality in Sport, 2026)
Background Chronic kidney disease (CKD) affects more than 10% of the global population and is associated with increased cardiovascular morbidity and mortality. Dyslipidemia contributes to CKD progression through inflammatory, atherosclerotic, and fibrotic mechanisms. Statins, widely used for lipid control, exhibit pleiotropic effects that may influence renal outcomes; however, their direct renoprotective role remains controversial. Aim To evaluate the efficacy and safety of statin therapy in patients with CKD, with particular emphasis on renal outcomes such as estimated glomerular filtration rate (eGFR) and proteinuria, and to analyze the molecular mechanisms underlying their pleiotropic effects. Material and Methods A literature review was conducted using PubMed, Google Scholar, ResearchGate, Embase, Scopus, and Web of Science. Relevant studies, including randomized controlled trials (PLANET I/II, SHARP, and CNODES) and meta-analyses, were selected according to predefined inclusion criteria. Results Statin therapy demonstrated a modest effect in slowing eGFR decline and reducing proteinuria; however, outcomes varied depending on the specific agent and dosage. Atorvastatin showed potential renoprotective effects, whereas high-dose rosuvastatin was associated with deterioration in renal function. High-intensity therapy may increase the risk of acute kidney injury and rare complications such as rhabdomyolysis, particularly in patients with CKD. Proposed molecular mechanisms include anti-inflammatory, antioxidant, and endothelial-protective effects. Conclusions Statins remain essential for reducing cardiovascular risk in patients with CKD; however, their renoprotective effects appear limited and are not uniform across all agents. Individualized therapy is crucial to balance cardiovascular benefits against potential renal risks. Further large-scale studies are needed to optimize treatment strategies in this population.